Phylloplane Yeasts on Cocoa and Their Abilities to Inhibit Phytophthora palmivora In Vitro - Ramadhani Mahendra Kusuma; Ahmad Ilham Tanzil; Soleudin Efendi (Jurnal Fitopatologi Indonesia, 2024)
Cocoa is an economically valuable plantation commodity, but its cultivation often faces a significant challenge, which is caused by the Phytophthora palmivora. Phylloplane yeast has an important role in protecting plant surfaces from pathogen infection. The aim of the study was to assess the diversity of phylloplane yeasts found on cocoa fruits, and determine them as biological control agents for P. palmivora. The metode include isolating yeasts from young, old and rotten cocoa pods and testing them as antagonists against P. palmivora. The findings of this study yielded eight yeast isolates that were significant in inhibiting the growth of P. palmivora. These isolates spanned across six genera, including Debaryomyces sp., Metschnikowia sp., Zygosaccharomyces sp., Candida sp., Wickerhamomyces sp., and Cryptococcus sp. Candida sp.2 and Wickerhamomyces sp. as particularly promising species species that had a consistently resistant level of inhibitory effect, achieved percentage inhibition of 36.26% (10.8 mm) and 34.44% (9.6 mm), respectively.